Association of 24-hour movement guideline adherence, mental health and quality of life in young adults: the role of e-Health literacy - Lin, Lixin; Liang, Wei; Wang, Runbin; Rhodes, Ryan E.; Liu, Huaxuan (Frontiers in Public Health, 2024)
Background The spread of Covid-19 and resultant infection prevention strategies have disturbed the life routine of Chinese young adults, led to reduced physical activity (PA), prolonged screen time (ST) and inadequate sleep duration (SP), and made immense influence on their mental health (MH) and quality of life (QoL). E-Health literacy (EHL) can enable citizens to use available online information to respond to the highly complex information environment and make appropriate health decisions. Objective This study aims to examine associations between adhering to 24-h movement (24HM) guidelines and MH and QoL among young adults, as well as to identify any mediating or moderating role of EHL in these associations. Methods 1742 young adults (20.03 ± 1.54 years old, 68.6% females) from north and south China completed self-report measures of 24HM (PA, ST and SP), health indicators (MH and QoL), EHL and demographic information through an online survey between 4 Apr and 16 Jun 2022. Generalized linear mixed models were applied for data analysis. Results Results showed that adhering to PA, ST and SP guidelines were all positively connected with QoL while MH was associated with adhering ST or SP guidelines. Adhering to more of 24HM guidelines was linked to better MH and QoL. EHL significantly mediated the association of guideline adherence and QoL and moderate that of guideline adherence and MH. Conclusion This is the first study to investigate the role of EHL on the associations between 24HM and MH as well as QoL during the Covid-19. The findings may contribute to further empirical research or intervention that aims to promote MH or QoL among young adults more effectively or provide valuable references for developing relevant strategies or policy of health promotion or public health events in China.